Finding the Connection: Research Data Management and the Office of Research. (2nd December 2016) - Rinehart, Amanda
Abstract : EDITOR'S SUMMARY Academic and research librarians can enhance the services they provide to researchers by collaborating with university offices of research. The requirement that projects have data management plans to qualify for federal funding has stimulated alignment, partnering and pooling of resources between service providers. The author's experiences in data librarian positions illustrate various routes and results of interaction, from demonstrating the value of reusing data for different purposes to promoting data ethics and best practices in data management. Librarians should seek out opportunities to collaborate with their campus research offices, understand commonalities in service to researchers and focus on data management as a complement to research professionals' work.